Acetone pretreatment for improvement of acetone, butanol, and ethanol production from sweet sorghum bagasse. (15th April 2016) - Jafari, Yadollah; Amiri, Hamid; Karimi, Keikhosro
Graphical abstract: Highlights: Production of ABE was significantly improved by acetone pretreatment. A high hydrolysis yield of 94.2% and sugar concentration of 36.3 g/L were obtained. More than 140 g lignin was removed from each kg SSB into the solvent. The solvent used for pretreatment of SSB, acetone, was produced from SSB. From one kg SSB, advanced biofuel equivalent to 72 g gasoline was produced. Abstract: Development of efficient and cost-effective pretreatment prior to hydrolysis is essential for the economical production of biobutanol from lignocelluloses. In this study, acetone pretreatment with a number of advantages over the other pretreatments was used to improve enzymatic hydrolysis and fermentation with Clostridium acetobutylicum for acetone–butanol–ethanol (ABE) production from sweet sorghum bagasse (SSB). Using the pretreatment at 180 °C for 60 min, the yield of enzymatic hydrolysis of SSB was improved to 94.2%, leading to a hydrolysate with 36.3 g/L total sugar, which was subsequently fermented to 11.4 g/L ABE. This process resulted in the production of 78 g butanol, 35 g acetone, 12 g ethanol, 28 g acetic acid, and 6 g butyric acid from each kg of SSB. Through the pretreatment, 143 g lignin per kg of SSB was dissolved into the solvent, with the potential to be recovered as unaltered pure lignin. Furthermore, the co-production of acetone by the ABE fermentation alleviated the concern about unavoidable solvent loss in the pretreatment, i.e., 24 g acetone/kg SSB, using an integrated process for biobutanol production from SSB. The energy equivalent obtained in the form of butanol and ethanol (72 g gasoline equivalent/kg SSB) was higher than that obtainable via ethanolic fermentation (less than 70 g/kg SSB).